Otherworlds - Byrne, Aisling (Oxford University Press, 2016)
'Otherworlds' offers a new perspective on the otherworlds depicted in British and Irish medieval literature.
10.1093/acprof:oso/9780198746003.001.0001
Keywords: English literature; Irish literature; Literature; Medieval; Fantasy in literature; History in literature